Comparison of growth and production of indigenous strain of the Mozambique Tilapia, oreochromis Mossambicus (Peters) - Nemutandani, Mashudu Lucky. (My University, 2006)
Refer to document
Thesis (M. A. (Aquaculture )) -- University of Limpopo, 2006
Keywords: Mozambique Tilapia; Aquacultural production; Fish growth; Aquarium Fish farming -- South Africa; Fish culture -- South Africa